Development of Indonesian Speaking Skills Teaching Materials for Foreign Speakers Based on Social and Cultural Contexts - Wita Septiani Rahmaputri; Annisa Widya Shafira; Annisa Faradilla; Salshabhina Dwi Febriyanti (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2025)
Global interest in learning the Indonesian language continues to increase; however, the availability of relevant and contextualized BIPA (Bahasa Indonesia for Foreign Speakers) teaching materials remains limited. Existing materials have not yet fully developed learners’ communicative competence or integrated Indonesia’s social and cultural contexts in depth. This study aims to develop socially and culturally based BIPA teaching materials to enhance foreign learners’ speaking skills through the social contexts of Indonesian society. The research employs the 4D development model (Define, Design, Develop, and Disseminate), adapted only to the first three stages: define, design, and develop. The definestage includes a needs analysis, a review of the BIPA Graduate Competency Standards (SKL), and an exploration of relevant Indonesian socio-cultural themes. The design stage focuses on structuring content, learning activities, and teaching strategies that encourage social interaction and communicative language use. The develop stage produces a prototype of socially and culturally based teaching materials that have been conceptually organized and are ready for expert validation and further testing in subsequent research. Data were collected through documentation studies and literature reviews. The results show that the designed materials, consisting of ten thematic units—including Natural Phenomena, Indonesian Culture, Social Media, Environment, and Social Issues—are theoretically aligned with the BIPA SKL and the CEFR framework. The developed product reflects the richness of Indonesia’s language and culture and has the potential to strengthen the communicative and intercultural competence of BIPA learners.